THEORETICAL BASIS OF DIVIDEND POLICY IN COMMERCIAL BANKS (Marketing Journal, 2025)
This article explores the theoretical foundations of dividend policy in commercial banks, emphasizing its alignment with evolving socio -economic conditions. It highlights the importance of managing credit risks, reducing non-performing loans, and developing new strategies to enhance dividend distribution. The study underlines the crucial role of lending in ensuring financial system stability. Furthermore, it presents the author’s proposals for improving financial decision -making and addressing problematic assets in banking operations.
Keywords: dividend; dividend policy; non-performing loans; banking operations; lending activities; financial decisions; financial assets; accounts receivable; accounts 297 payable; non-financial assets; real assets; cash flows; bank financial strategy; financial security; strategic management